Gambaran tingkat pengetahuan dan perilaku tentang pemeriksaan payudara sendiri (SADARI) pada remaja putri di wilayah kerja UPT Puskesmas Blahbatuh II Gianyar Bali Indonesia - Karen Singam; I B Wirakusuma (Intisari Sains Medis, 2017)
Worldwide, breast cancer is amongst the leading cause of morbidity and mortality in women. Â Early detection and diagnosis is key in acquiring a better prognosis and can be achieved through self breast examination (SADARI). This was a cross sectional descriptive study. A senior high school was chosen at random to select samples from and that is SMA PGRI Blahbatuh and 50 samples were chosen at random. The instrument used to conduct this study was a questioner that was adapted from a few different questioners of the same nature. From the collected data, there were 0% teenage girls at the work territory of UPT Kesmas Blahbatuh II that has good knowledge about breast cancer and self breast examination. The majority has lesser (88%) knowledge and (98%) practice about self breast examination (SADARI). Also, there is a possibility for 100% of teenage girls that have inadequate SADARI knowledge to have inadequate SADARI practice. Teenage girls at the age â‰¤16 years old have 89.7% of inadequate SADARI knowledge and 96.6% have the possibility to have inadequate SADARI practice. Because of the low and inadequate knowledge and practice in regards to SADARI, it is hoped that the Puskemas provide enlightment and awareness towards breast cancer and self breast examination (SADARI) for teenage girls and women in the working district of the health centre.Â